Propagation measurements and prediction of bwa based on downtilting antenna - 489537 Mohamud Omar Jama; Fakulti Kejuruteraan Elektrik (2009)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2009